Environmental factors in agricultural production of Malaysia - Mokhtaruddin, A. M.; Jamal, T.
The distribution of rainfall and the length of dry period are the two main environmental factors influencing agricultural production of Malaysia. The effect of these climatic parameters on the growth and yield of major parennial and lowland crops of Malaysia is discussed. Finally their use in drawing up the agroecological zones is reviewed.